Characteristics of recurrence in adult- type granulosa cell tumor. Issue 4 (1st July 2008) - Lee, Y.-K.; Park, N.-H.; Kim, J. W.; Song, Y.-S.; Kang, S.-B.; Lee, H.-P.
Abstract : Granulosa cell tumor (GCT) of the ovary is a very rare neoplasm, which is characterized by an indolent clinical course. Thus, the clinical characteristics, optimal treatment, and follow-up protocols are not well established. The goal of this study is to evaluate clinical findings, prognostic factors, and recurrent features of GCT in Korean patients. Between 1987 and 2005, 42 cases of GCT were diagnosed in our institution. There were 35 cases showing adult-type GCT, which were available for evaluation. All charts were reviewed, and the clinical data along with treatment results were retrospectively studied. Statistical analyses were performed for risk factors of recurrence and disease-free survival. GCT accounted for 3% of all ovarian malignancies in our institution during the study period. The median age was 45 years (range, 24–68 years). Abdominal and hormone-related symptoms were the main causes of first presentation. There were eight cases of recurrence including two cases of disease-related deaths during the median follow-up period of 177 months (range, 8–212 months). Factors affecting the recurrence involved residual tumor and stage, but residual tumor was the only significant factor of recurrence in multivariate analysis. The median time to relapse was 75 months (range, 55–137 months), and the liver was the most common extra-pelvic metastatic site followed by the intestine. Continuous long-term follow-up with pelvic and whole-abdominal surveillance is absolutely required. Active management including complete tumorectomy is the most important treatment modality in both primary surgeries and recurrent cases.